IMPLEMENTASI CHANGE MANAGEMENT MENGGUNAKAN AWARENESS, DESIRE, KNOWLEDGE, ABILITY, REINFORCEMENT (ADKAR) APPROACH DALAM MENINGKATKAN KINERJA PEGAWAI - Nabiela, Noorsy Zidna; Yuana, Pusvita; Armanu, Armanu (Jurnal Kewirausahaan dan Inovasi, 2022)
This research aims to analyze the effect of Awareness, Desire, Knowledge, Ability, Reinforcement (ADKAR) on employees performance at KPw Bank Indonesia Malang. This type of research is quantitative research using purposive sampling, as many as 42 respondents. Data collection techniques were carried out by observation, interviews and distributing questionnaires. Data analysis used classical assumption test, multiple regression analysis, F test, and T test using SPSS 23 software for windows. The results showed that the Employee Change Program at Kpw Bank Indonesia Malang included BI Religion, BI Achievement, BI Innovation, BI Digital and the influence of change management on the variables of Awareness, Desire, Knowledge, Ability, Reinforcement (ADKAR) each have a positive and significant effect on the performance of employees of KPw Bank Indonesia Malang.